Gut microbiota-generated short-chain fatty acids are involved in para-chlorophenylalanine-induced cognitive disorders - Liu, Yanbo; Li, Zhen; Sun, Tianning; He, Zhigang; Xiang, Hongbing; Xiong, Jun (Frontiers in Microbiology, 2022)
Neurocognitive disorders (NCDs) include complex and multifactorial diseases that affect several individuals. The 5-hydroxytryptamine (5-HT) neuron system plays an important role in NCDs. Existing studies have reported that para-chlorophenylalanine (PCPA), a 5-HT scavenger, has a negative effect on cognitive function. However, we believe that PCPA may result in NCDs through other pathways. To explore this possibility, behavioral tests were performed to evaluate the cognitive function of PCPA-treated mice, suggesting the appearance of cognitive dysfunction and depression-like behavior. Furthermore, 16S rRNA and metabolomic analyses revealed that dysbiosis and acetate alternation could be related to PCPA-induced NCDs. Our results suggest that PCPA impairs cognition via 5-HT depletion and dysbiosis induction and that the latter promotes NCDs by reducing short-chain fatty acid levels. Together, these findings provide an alternative perspective on PCPA-induced NCDs.